Penjaminan Mutu Tenaga Kependidikan Dalam Meningkatkan Mutu Pendidikan SMPN 34 Surabaya - Zahra, Nadia Lailatuz; Safa Felisa, Adinda; Windasari, Windasari; Hanivia Cindy, Agustin (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2024)
Quality assurance is a series of processes and systems related to collecting, analyzing, and reporting data on the performance and quality of teaching and education personnel, programs and institutions. Collaborative efforts between leaders of educational institutions, academic staff and administrative staff are needed to ensure effective implementation of quality assurance of education personnel.The quality assurance process identifies aspects of achievement and improvement priorities, provides data as a basis for planning and decision making and helps build a culture of continuous improvement.The regional autonomy policy has an impact on education management in the regions. Quality standardization efforts must be the focus of attention in an effort to maintain the quality of education nationally. The quality assurance and improvement system for primary and secondary education in Indonesia operates within an education management and governance system that delegates much of the responsibility for implementation to provinces, districts, foundations and schools/madrasas. The achievement of educational quality for primary and secondary education is assessed based on the eight National Education Standards of BSNP.